Analisis Framing Pemberitaan Kasus Korupsi Tom Lembong dalam Bingkai Media Online Antaranews.com dan Tempo.co - Eric Raynaldo Handy Saputra; Hanna Nurhaqiqi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study analyzes the framing of news coverage on the alleged corruption case involving Tom Lembong related to the 2015 sugar import policy, as reported by Antaranews.com and Tempo.co. The case drew attention because it involved a political figure in opposition to the government, raising suspicions of legal politicization ahead of the 2024 elections. This research aims to examine how both media outlets framed the case. Antaranews.com and Tempo.co were chosen due to different ownership structures: Antaranews.com is state-owned under BUMN, while Tempo.co is privately and publicly owned. The study uses Robert Entman’s framing analysis model, covering four elements: define problems, diagnose causes, make moral judgments, and treatment recommendations. The findings are connected to Michel Foucault’s theory of power relations. News articles were collected using the keyword “Tom Lembong” from October 29 to November 30, 2024, yielding 51 articles from Antaranews.com and 154 from Tempo.co. These were further filtered by stages of the case: suspect naming, political responses, pretrial & alleged politicization, and pretrial rejection. From this, 5 articles from Antaranews.com and 6 from Tempo.co were selected as the most representative. The results show clear differences. Antaranews.com emphasizes the legality of the Attorney General’s actions, supports the legitimacy of the legal process, and relies on official sources. Meanwhile, Tempo.co frames the case more critically, questioning the legal process and highlighting broader political narratives. These differences reflect power relations that influence media framing according to ownership.